Lola at the library ebook - McQuinn, Anna (Lola., 2011)
Lola has a big smile on her face. Why? Because it's Tuesday — and on Tuesdays, Lola and her mommy go to the library. Join Lola in this cozy celebration of books and the people who love them. Lola at the Library was originally published in Great Britain and there it is called Lulu at the Library. Author Anna McQuinn is a librarian in England.